MAGNITUDE OF CORRUPTION, RATIONALIZATION, AND INTERNAL CONTROL QUALITY: AN EXPERIMENTAL STUDY ON SUBSEQUENT OFFENSE - Nahartyo, Ertambang; Haryono, Haryono (Jurnal Akuntansi dan Keuangan Indonesia, 2018)
This research examines the extent to which the rationalization tactics model reflects the relation between magnitude of corruption and attitudes toward corruption. The rationalization model predicts that individuals will justify their corrupt acts and that rationalizations will affect subsequent offense depending upon the levels of internal control quality. Using a 2 X 2 between-subjects experiment with 170 public servants as participants, this research finds that individuals are more prone to accept and rationalize their corrupt acts in the gratuities context than in the bribery context. Further, this research finds that rationalizations lead to subsequent offense. However, this study cannot find support on the mitigating effect of internal control quality. The results point to the importance of considering the implications of organizational culture for future effective combat against corruption.